Evaluation of maize core collection for drought tolerance - Teixeira,Flavia França (2010)
The maize genebank (GBmaize) preserves nearly 4,000 accessions for conservation and use. The use is however restricted because the accessions do not perform as well as the elite genotypes. This problem can be reduced by pre-breeding, i.e., by extending the information on germplasm and introgressing useful alleles. Since irregular rainfall distribution and drought induce maize yield losses, drought tolerance is a main breeding target. In this study, the GBmaize accessions were evaluated for drought tolerance. Environmental factors, genotypes and the respective interactions influence the phenotypic expression. There was however no interaction genotype - irrigation level, so no accessions with different performance under the two water regimes could be identified. The performance of the following accessions was promising for a number of traits: SP154, BA166, MG099, CE002, SE025, BA154, BA194, BA085, MG076, PR053, Roxo Macapá, SE016, and AL018.